Electrolyte, battery and electric equipment
By using fluorovinyl carbonate and 2-[N,N-bis(trifluoromethanesulfonyl)amino]pyridine as additives in the electrolyte, the first effect of the battery after increasing the specific surface area of the negative electrode and the lithium embedded rate is solved. and the problem of poor circulation performance, the battery's high efficiency and good cycle stability are achieved.
Patent Information
- Application Number
- CN202411719399.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-27
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-11-27
AI Technical Summary
While increasing the specific surface area of the negative electrode and the lithium embedded rate, the battery has a low first effect and poor circulation performance. This is mainly due to the increase in the side reaction between the negative electrode and the electrolyte, which leads to excessive consumption of active lithium.
By using fluorovinyl carbonate and 2-[N,N-bis(trifluoromethanesulfonyl)amino]pyridine in the electrolyte, SEI films are formed and fluorine ions and lithium ions are slowed down respectively in the electrolyte. Combination, thereby reducing the loss of active lithium.
The battery has good cycling performance in low and high temperature environments, and the first charge and discharge efficiency and energy density are improved.
Smart Images

Figure CN119481273A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of battery technology, and in particular to an electrolyte, a battery and an electrical device. Background Art
[0002] With the rapid development of new energy technologies, the requirements for the capacity and energy efficiency of energy storage batteries are getting higher and higher. In order to improve the energy efficiency of batteries, the specific surface area of the negative electrode is usually increased, the active sites of the graphite surface reaction are increased, and the negative electrode particle size is reduced, and the graphite lithium insertion rate is increased to improve the energy efficiency of the electrode assembly. However, as the specific surface area of the negative electrode increases, the side reactions between the negative electrode and the electrolyte increase during the battery formation film formation, resulting in more active lithium consumption, resulting in a loss of battery capacity, which makes the battery's initial efficiency low and the cycle performance poor. Summary of the invention
[0003] In view of this, the present application provides an electrolyte, a battery and an electrical device. The electrolyte reduces the loss of active lithium through the interaction of a first additive and a second additive, and can form a film on the surface of a negative electrode plate better, so that the battery has a higher initial charge and discharge efficiency, energy density and better cycle stability.
[0004] The present application provides an electrolyte, which includes: a first additive and a second additive, wherein the first additive includes fluoroethylene carbonate, and the second additive includes 2-[N,N-bis(trifluoromethanesulfonyl)amino]pyridine.
[0005] Furthermore, the mass fraction of the first additive is a, and the mass fraction of the second additive is b, then the electrolyte satisfies the relationship: 1<a / b≤10.
[0006] Furthermore, the mass fraction a of the first additive is in the range of 0.1%≤a≤3%.
[0007] Furthermore, the mass fraction b of the second additive is in the range of 0.05%≤b≤2%.
[0008] The present application also provides a battery, which includes an electrode assembly and an electrolyte provided in the present application, wherein the electrode assembly includes a negative electrode plate; and the electrolyte is used to infiltrate at least a portion of the electrode assembly.
[0009] Furthermore, in the electrolyte, the mass fraction of the first additive is a, the mass fraction of the second additive is b; the negative electrode plate includes a negative electrode current collector layer and a negative electrode material layer stacked, the negative electrode material layer includes active particles, and the specific surface area of the active particles is S, then the battery satisfies the relationship: 0.2g / m 2≤100(a+b) / S≤8g / m 2 .
[0010] Furthermore, the specific surface area S of the active particles is in the range of: 0.8 m 2 / g≤S≤2.5m 2 / g.
[0011] Furthermore, in the electrolyte, the mass fraction of the first additive is a, and the mass fraction of the second additive is b; the negative electrode plate includes a stacked negative electrode current collector layer and a negative electrode material layer, the negative electrode material layer includes active particles, and the median particle size of the active particles is D, then the battery satisfies the relationship: 3μm≤D / 100(a+b)≤16μm.
[0012] Furthermore, the range of the median particle size D of the active particles is: 5 μm≤D≤20 μm.
[0013] The present application also provides an electrical device, which includes a device body and a battery provided in the present application, and the battery supplies power to the device body.
[0014] In the present application, the electrolyte includes a first additive and a second additive, the first additive includes fluoroethylene carbonate, the first additive is a film-forming additive, when the electrolyte is applied to the battery and the battery is formed, the first additive undergoes a reduction reaction and decomposes, and the decomposition product forms an SEI film on the surface of the negative electrode plate, and the SEI film formed by the first additive has a stable structure, so that the battery has good cycle performance in both low temperature and high temperature environments. In addition, during the charge and discharge cycle of the battery, the first additive can repair the SEI film to maintain the stability of the interface film formed by the first additive on the surface of the negative electrode plate. However, in the first additive, the carbon-fluorine bond in fluoroethylene carbonate is easy to break, so that the fluoride ions and ethylene carbonate molecules are easily separated from the first additive, and the fluoride ions are easy to combine with active ions such as lithium ions in the electrolyte to form lithium fluoride, thereby consuming the active lithium ions in the electrolyte and reducing the initial charge and discharge efficiency and energy density of the battery. Furthermore, the electrolyte of the present application also includes a second additive, which includes 2-[N,N-bis(trifluoromethanesulfonyl)amino]pyridine. The trifluoromethyl group in 2-[N,N-bis(trifluoromethanesulfonyl)amino]pyridine has a strong electron-withdrawing effect, so that the electron cloud density of the second additive is biased towards the trifluoromethyl molecule, and the electronegativity of the nitrogen atom is greater than the electronegativity of the carbon atom. Therefore, during the initial film formation, the CN bond in the second additive is broken to form pyridine carbon cations and N,N-bis(trifluoromethanesulfonyl). When the first additive and the second additive are mixed and distributed in the electrolyte, the pyridine carbon cation combines with the fluoride ion to form 2-fluoropyridine, thereby reducing the free fluoride ions in the electrolyte and slowing down the combination of fluoride ions and lithium ions to avoid fluoride ions consuming lithium ions in the electrolyte, so that the battery has a higher initial charge and discharge efficiency and energy density. In addition, 2-fluoropyridine has a higher reaction activity than the first additive, and is easier to decompose and form a film on the surface of the negative electrode, and N, N-bistrifluoromethanesulfonyl can promote the ring opening and decomposition of ethylene carbonate molecules into a film. In other words, the first additive and the second additive are compounded, and during the first formation and film formation process of the battery, they can be decomposed and formed into a film on the surface of the negative electrode to form an inorganic and organic composite interface film containing N, F and C, so that the battery has better cycle stability. Furthermore, the first additive and the second additive have a higher content of inorganic components in the interface film formed on the surface of the negative electrode, so that the battery has better high-temperature cycle stability. The electrolyte of the present application reduces the loss of active lithium through the interaction of the first additive and the second additive, and can form a film on the surface of the negative electrode, so that the battery has both higher initial charge and discharge efficiency, energy density and better cycle stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the implementation will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0016] Figure 1 A schematic diagram of the structure of a battery according to an embodiment of the present application;
[0017] Figure 2 This is a schematic diagram of the structure of an electrical device according to an embodiment of the present application;
[0018] Figure 3 This is a circuit block diagram of an electrical device according to an embodiment of the present application.
[0019] Description of reference numerals:
[0020] 100 - battery, 110 - electrode assembly, 111 - negative electrode plate, 112 - diaphragm, 113 - positive electrode plate, 120 - electrolyte, 200 - electrical equipment, 210 - equipment body. DETAILED DESCRIPTION
[0021] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.
[0022] The terms "first", "second", etc. in the specification and claims of this application and the above-mentioned drawings are used to distinguish different objects, rather than to describe a specific order. In addition, the terms "including" and "having" and any variations thereof are intended to cover non-exclusive inclusions. For example, a process, method, system, product or device that includes a series of steps or units is not limited to the listed steps or units, but optionally includes steps or units that are not listed, or optionally includes other steps or units inherent to these processes, methods, products or devices.
[0023] Reference to "embodiment" or "implementation" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiment or implementation may be included in at least one embodiment of the present application. The appearance of the phrase in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments.
[0024] With the rapid development of new energy technologies, the requirements for the capacity and energy efficiency of energy storage batteries are getting higher and higher. In order to improve the energy efficiency of batteries, the specific surface area of the negative electrode is usually increased, the active sites of the graphite surface reaction are increased, and the negative electrode particle size is reduced, and the graphite lithium insertion rate is increased to improve the energy efficiency of the electrode assembly. However, as the specific surface area of the negative electrode increases, the side reactions between the negative electrode and the electrolyte increase during the battery formation film formation, resulting in more active lithium consumption, resulting in a loss of battery capacity, which makes the battery's initial efficiency low and the cycle performance poor.
[0025] Specifically, during the formation of the SEI film in the battery, the additives in the electrolyte decompose and form a film on the surface of the negative electrode, which consumes a certain amount of active lithium and causes capacity loss. Therefore, it is necessary to propose a solution that can increase the specific surface area of the negative electrode and reduce the particle size of the negative electrode without deteriorating the initial efficiency and cycle performance of the battery.
[0026] It can be understood that in the terminology of this application, "SEI membrane" is Solid Electrolyte Interface membrane, that is, solid electrolyte interface membrane, which is located at the interface between the battery electrode (such as the negative electrode plate) and the electrolyte.
[0027] See also Figure 1 The present application provides an electrolyte 120, which includes: a first additive and a second additive, wherein the first additive includes fluoroethylene carbonate, and the second additive includes 2-[N,N-bis(trifluoromethanesulfonyl)amino]pyridine.
[0028] It can be understood that the electrolyte 120 is applied to the battery 100 , and the battery 100 includes an electrode assembly 110 , and the electrolyte 120 is used to wet at least a portion of the electrode assembly 110 , and the electrode assembly 110 includes a negative electrode plate 111 .
[0029] It can be understood that the structural formula of 2-[N,N-bis(trifluoromethanesulfonyl)amino]pyridine is
[0030] In this embodiment, the electrolyte 120 includes a first additive and a second additive, the first additive includes fluoroethylene carbonate, and the first additive is a film-forming additive. When the electrolyte 120 is applied to the battery 100 and the battery 100 is formed, the first additive undergoes a reduction reaction and decomposes, and the decomposition product forms an SEI film on the surface of the negative electrode plate 111. The SEI film structure formed by the first additive is stable, so that the battery 100 has good cycle performance in both low temperature and high temperature environments. In addition, during the charge and discharge cycle of the battery 100, the first additive can repair the SEI film to maintain the stability of the interface film formed by the first additive on the surface of the negative electrode plate 111. However, in the first additive, the carbon-fluorine bond in fluoroethylene carbonate is easy to break, so that the fluoride ions and ethylene carbonate molecules are easily separated from the first additive, and the fluoride ions are easy to combine with the active ions such as lithium ions in the electrolyte 120 to form lithium fluoride, thereby consuming the active lithium ions in the electrolyte 120, reducing the initial charge and discharge efficiency and energy density of the battery 100. Furthermore, the electrolyte 120 of the embodiment of the present application also includes a second additive, which includes 2-[N,N-bis(trifluoromethanesulfonyl)amino]pyridine. The trifluoromethyl group in 2-[N,N-bis(trifluoromethanesulfonyl)amino]pyridine has a strong electron-withdrawing effect, so that the electron cloud density of the second additive is biased towards the trifluoromethyl molecule, and the electronegativity of the nitrogen atom is greater than the electronegativity of the carbon atom. Therefore, during the initial film formation, the CN bond in the second additive is broken to form pyridine carbon cations and N,N-bis(trifluoromethanesulfonyl). When the first additive and the second additive are mixed and distributed in the electrolyte 120, the pyridine carbon cation combines with the fluoride ion to form 2-fluoropyridine, thereby reducing the free fluoride ions in the electrolyte 120 and slowing down the combination of fluoride ions and lithium ions to avoid fluoride ions consuming lithium ions in the electrolyte 120, so that the battery 100 has a higher initial charge and discharge efficiency and energy density. In addition, 2-fluoropyridine has a higher reactivity than the first additive, and is easier to decompose into a film on the surface of the negative electrode plate 111, and N, N-bistrifluoromethanesulfonyl can promote the ring opening and decomposition of ethylene carbonate molecules into a film. In other words, the first additive and the second additive are compounded, and during the first formation of the film of the battery 100, they can be decomposed into a film on the surface of the negative electrode plate 111 to form an inorganic and organic composite interface film containing N, F and C, so that the battery 100 has good cycle stability. Furthermore, the first additive and the second additive have a high content of inorganic components in the interface film formed on the surface of the negative electrode plate 111, so that the battery 100 has good high-temperature cycle stability.The electrolyte 120 of this embodiment reduces the loss of active lithium and forms a good film on the surface of the negative electrode plate 111 through the interaction of the first additive and the second additive, so that the battery 100 has a higher initial charge and discharge efficiency, energy density and better cycle stability.
[0031] It can be understood that in the terminology of the present application, "formation" refers to the process of activating the active materials of the internal positive electrode plate 113 and the negative electrode plate 111 of the battery 100 through a certain charging and discharging method after the battery 100 is manufactured, so as to improve the charging and discharging performance and comprehensive performance of the battery 100 such as self-discharge and storage.
[0032] It can be understood that in the terminology of the present application, the higher the "reactivity", the easier it is to react. For example, during the charging process of the battery 100, the potential of the positive electrode plate 113 increases and the potential of the negative electrode plate 111 decreases. If the reduction potential on the negative electrode plate 111 side is higher, it means that the reduction decomposition reaction occurs more preferentially on the negative electrode plate 111. In this embodiment, the product 2-fluoropyridine formed by the pyridine carbon cation and the fluoride ion has a higher reduction potential on the negative electrode plate 111 side than the first additive.
[0033] Specifically, the reduction potential of the first additive on the negative electrode plate 111 side is about 1.2V, the reduction potential of the second additive on the negative electrode plate 111 side is about 1.5V and about 1.98V, and the reduction potential of the product 2-fluoropyridine formed by the first additive and the second additive on the negative electrode plate 111 side is higher than 1.2V.
[0034] In some embodiments, the mass fraction of the first additive is a, the mass fraction of the second additive is b, and the electrolyte 120 satisfies the relationship: 1<a / b≤10.
[0035] Specifically, the value of a / b can be, but is not limited to, 1.5, 2, 2.5, 3, 3.6, 4, 4.7, 5, 5.5, 6, 6.5, 7, 7.3, 8, 8.6, 9, 9.6 and 10, etc.
[0036] It can be understood that, in the electrolyte 120 , the mass fraction of the first additive is greater than the mass fraction of the second additive.
[0037] When the electrolyte 120 satisfies the relationship 1<a / b≤10, the mass fraction of the first additive and the mass fraction of the second additive in the electrolyte 120 are both within a reasonable range, and the mass fraction of the first additive is greater than the mass fraction of the second additive. On the one hand, during the formation stage of the battery 100, the first additive and the second additive are compounded, and the number of pyridinium carbon cations separated from the second additive and the number of N,N-bistrifluoromethanesulfonyl are both within a reasonable range. The pyridinium carbon cations of the second additive are combined with the fluoride ions separated from the first additive to reduce the free fluoride ions in the electrolyte 120, so that the battery 100 has a higher initial charge and discharge efficiency and energy density. In addition, the product of the combination of the first additive and the second additive, 2-fluoropyridine, has a higher reactivity than the first additive, and is easier to decompose into a film on the surface of the negative electrode plate 111, and N, N-bistrifluoromethanesulfonyl can promote the ring opening and decomposition of ethylene carbonate molecules into a film. In other words, the first additive and the second additive are compounded, and during the first formation of the film of the battery 100, they can be decomposed into a film on the surface of the negative electrode plate 111 to form an inorganic and organic composite interface film containing N, F and C, so that the battery 100 has better cycle stability. On the other hand, during the subsequent charge and discharge cycles of the battery 100, the first additive can repair the SEI film in time to maintain the structural integrity of the SEI film, thereby ensuring the cycle stability of the battery 100. When the value of a / b is too large, the mass fraction of the first additive in the electrolyte 120 is too large, or the mass fraction of the second additive is too small. Although the first additive can promote the formation of the SEI film, the first additive separates too many fluorine ions, and the second additive separates too few pyridinium cations. The pyridinium cations are insufficient to combine with the fluorine ions one by one, so that there are still free fluorine ions in the electrolyte 120. The fluorine ions will combine with the lithium ions in the electrolyte 120 to form lithium fluoride, causing the loss of lithium ions in the electrolyte 120, so that when the electrolyte 120 is applied to the battery 100, the initial charge and discharge efficiency and energy density of the battery 100 are low. When the value of a / b is too small, the mass fraction of the first additive in the electrolyte 120 is too small, or the mass fraction of the second additive is too large. When the mass fraction of the first additive is too small, in the subsequent charge and discharge cycle of the battery 100, it is difficult for the first additive to repair the SEI film, thereby reducing the structural stability of the SEI film, resulting in poor cycle stability of the battery 100.When the mass fraction of the second additive is too large, the second additive separates too much 2-fluoropyridine, and the pyridine carbon cations in the second additive and the fluoride ions in the first additive form too much 2-fluoropyridine, which will increase the impedance of the interface film between the negative electrode plate 111 and the electrolyte 120, thereby reducing the energy efficiency of the battery 100.
[0038] In some embodiments, the mass fraction a of the first additive is in the range of 0.1%≤a≤3%.
[0039] Specifically, the mass fraction a of the first additive may be, but is not limited to, 0.1%, 0.3%, 0.5%, 0.8%, 1%, 1.2%, 1.5%, 1.8%, 2%, 2.2%, 2.4%, 2.6%, 2.8% and 3%, etc.
[0040] When the mass fraction a of the first additive satisfies the range of 0.1%≤a≤3%, the mass fraction a of the first additive is within a reasonable range, and the mass proportion of the first additive in the electrolyte 120 is within a reasonable range. On the one hand, during the formation stage of the battery 100 and the subsequent charge and discharge cycle, the first additive can be combined with the second additive to form a SEI film on the surface of the negative electrode plate 111, and the first additive can repair the SEI film so that the SEI film has better structural stability. On the other hand, it can prevent the first additive from separating too many fluoride ions and prevent the first additive from losing too many lithium ions, so that when the electrolyte 120 is applied to the battery 100, the battery 100 has both higher initial charge and discharge efficiency, higher energy density and better cycle stability. When the mass fraction a of the first additive is too large, the mass proportion of the first additive in the electrolyte 120 is too large, and the amount of fluoride ions decomposed by the first additive is too large. Even if the electrolyte 120 includes the second additive, it is difficult to combine with all the fluoride ions separated by the first additive, so that there are still many free fluoride ions in the electrolyte 120, which will consume the lithium ions in the electrolyte 120, thereby reducing the initial charge and discharge efficiency and energy density of the battery 100. When the mass fraction a of the first additive is too small, the mass proportion of the first additive in the electrolyte 120 is too small, and in the subsequent charge and discharge cycle of the battery 100, it is difficult for the first additive to repair the SEI film, thereby reducing the structural stability of the SEI film, and making the cycle stability of the battery 100 poor.
[0041] In some embodiments, the mass fraction b of the second additive is in the range of 0.05%≤b≤2%.
[0042] Specifically, the mass fraction b of the second additive can be but is not limited to 0.05%, 0.08%, 0.1%, 0.15%, 0.2%, 0.3%, 0.5%, 0.8%, 1%, 1.2%, 1.3%, 1.5%, 1.7%, 1.8% and 2%, etc.
[0043] When the mass fraction b of the second additive satisfies the range of 0.05%≤b≤2%, the mass fraction b of the second additive is within a reasonable range. Then, in the electrolyte 120, the mass proportion of the second additive is within a reasonable range, and the amount of pyridinium carbon cations and N,N-bistrifluoromethanesulfonyl separated by the second additive is within a reasonable range. On the one hand, the pyridinium carbon cations can be combined with the fluoride ions separated by the first additive to form 2-fluoropyridine to consume the free fluoride ions in the electrolyte 120, thereby avoiding excessive lithium ion loss during the film formation process of the first additive, and avoiding excessive generation of 2-fluoropyridine to increase the internal resistance of the battery 100, so that when the electrolyte 120 is applied to the battery 100, the battery 100 has higher initial charge and discharge efficiency, energy density and energy efficiency. On the other hand, N,N-bis(trifluoromethanesulfonyl) can promote the ring opening and decomposition of the ethylene carbonate molecules decomposed by the first additive into a film. In other words, the first additive and the second additive are compounded, and can be decomposed into a film on the surface of the negative electrode plate 111 during the first formation of the film of the battery 100, forming an inorganic and organic composite interface film containing N, F and C, so that the battery 100 has good cycle stability. When the mass fraction b of the second additive is too large, the mass proportion of the second additive in the electrolyte 120 is too large, and the pyridine carbon cations in the second additive and the fluorine ions of the first additive form too much 2-fluoropyridine, which will increase the impedance of the interface film between the negative electrode plate 111 and the electrolyte 120, thereby reducing the energy efficiency of the battery 100 and worsening the rate performance of the battery 100. When the mass fraction b of the second additive is too small, correspondingly, in the electrolyte 120, the mass proportion of the second additive is too small, and the pyridinium cations separated by the second additive are too few, so that the pyridinium cations can only combine with a small part of the fluoride ions. In other words, there are still many free fluoride ions in the electrolyte 120, so that the fluoride ions combine with the lithium ions in the electrolyte 120 and consume the lithium ions, thereby reducing the initial charge and discharge efficiency and energy density of the battery 100 when the electrolyte 120 is applied to the battery 100.
[0044] Preferably, the mass fraction b of the second additive is in the range of 0.01%≤b≤1%.
[0045] Optionally, the electrolyte 120 also includes a solvent, which is used to dissolve the first additive and the second additive, and the solvent is selected from at least one of ethylene carbonate, propylene carbonate, diethyl carbonate, ethyl methyl carbonate, dimethyl carbonate, ethyl acetate, ethyl propionate, propyl propionate, 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether, and ethylene glycol dimethyl ether.
[0046] Optionally, the electrolyte 120 further includes a lithium salt, which is dissolved in a solvent and is selected from at least one of lithium hexafluorophosphate, lithium difluorosulfonyl imide, lithium difluorooxalatoborate, lithium bisoxalatoborate, lithium tetrafluoroborate, and lithium trifluoromethylsulfonyl imide. The lithium salt has a high lithium content to provide active lithium ions for the electrolyte 120, thereby improving the energy density of the battery 100 when the electrolyte 120 is applied to the battery 100.
[0047] The present application also provides a battery 100 , which includes an electrode assembly 110 and an electrolyte 120 provided in the present application. The electrode assembly 110 includes a negative electrode plate 111 ; the electrolyte 120 is used to soak at least a portion of the electrode assembly 110 .
[0048] Optionally, in some embodiments, the battery 100 is a lithium-ion battery.
[0049] It can be understood that the electrode assembly 110 also includes a positive electrode plate 113. During the charging process of the battery 100, lithium ions are released from the positive electrode plate 113 and embedded in the negative electrode plate 111 through the electrolyte 120; during the discharging process of the battery 100, lithium ions are released from the negative electrode plate 111 and embedded in the positive electrode plate 113 through the electrolyte 120.
[0050] In the battery 100 provided in this embodiment, the electrolyte 120 is used to infiltrate at least a portion of the electrode assembly 110 to achieve ion transmission between the electrolyte 120 and the electrode assembly 110. The electrolyte 120 includes a first additive and a second additive, and the second additive can consume the fluoride ions separated by the first additive in a timely manner, so that even if the negative electrode plate 111 has a large specific surface area, it can slow down the combination of the fluoride ions and lithium ions, thereby avoiding the consumption of active lithium in the battery 100, and the battery 100 has a high first charge and discharge efficiency and energy density. In addition, the first additive and the second additive are compounded to form an inorganic and organic composite interface film containing N, F and C on the surface of the negative electrode plate 111, so that the battery 100 has good cycle stability.
[0051] Optionally, the electrode assembly 110 further includes a separator 112 , and the positive electrode plate 113 , the separator 112 , and the negative electrode plate 111 are stacked.
[0052] Optionally, in the electrolyte 120 , the mass fraction a of the first additive and the mass fraction b of the second additive satisfy the relationship: 0.15%≤a+b≤5%.
[0053] It can be understood that a+b may represent the ratio of the sum of the mass of the first additive and the mass of the second additive to the mass of the electrolyte 120 .
[0054] Specifically, the value of a+b can be but is not limited to 0.15%, 0.8%, 1%, 1.2%, 1.9%, 2%, 2.3%, 2.7%, 3%, 3.2%, 3.6%, 4%, 4.2%, 4.7% and 5%, etc.
[0055] In this embodiment, when the mass fraction a of the first additive and the mass fraction b of the second additive satisfy 0.15%≤a+b≤5%, in the electrolyte 120, the mass fraction a of the first additive and the mass fraction b of the second additive are within a reasonable range, and the first additive and the second additive are compounded, which can not only slow down the fluorine ions separated by the first additive and the lithium ions in the electrolyte 120 to avoid excessive consumption of lithium ions, but also form a stable SEI film on the surface of the negative electrode plate 111, so that the battery 100 has both high energy density, initial charge and discharge efficiency and energy efficiency. When the value of a+b is too large, the total sum of the mass fraction a of the first additive and the mass fraction b of the second additive is too large. When the mass fraction a of the first additive is too much, it may cause too many fluorine ions separated by the first additive. Even if the content of the second additive is high, it is difficult to slow down the combination of fluorine ions and lithium ions. In addition, if the mass fraction of the second additive is large enough, the product formed by the second additive and the fluorine ions will also increase the impedance of the battery 100, thereby reducing the energy efficiency of the battery 100. When the value of a+b is too small, the sum of the mass fraction a of the first additive and the mass fraction b of the second additive is too small, then the first additive is too little and / or the second additive is too little. When the first additive is too little, it is difficult for the electrolyte 120 to form an SEI film on the surface of the negative electrode plate 111, and in the subsequent charge and discharge cycle process, it is difficult for the first additive to repair the SEI film in time, thereby reducing the cycle stability of the battery 100. When the second additive is too little, it is difficult for the second additive to bind the fluoride ions shed by the first additive, thereby it is difficult to slow down the consumption of active lithium in the electrolyte 120, so that the initial charge and discharge efficiency and energy density of the battery 100 are low.
[0056] In some embodiments, the negative electrode plate 111 includes a negative electrode current collector layer and a negative electrode material layer stacked together, the negative electrode material layer includes active particles, the specific surface area of the active particles is S, and the specific surface area S of the active particles is in the range of: 0.8m 2 / g≤S≤2.5m 2 / g.
[0057] Specifically, the specific surface area S of the active particles may be, but is not limited to, 0.8 m 2 / g, 0.9m 2 / g, 1m 2 / g, 1.2m 2 / g, 1.3m 2 / g, 1.4m 2 / g, 1.5m 2 / g, 1.6m 2 / g, 1.7m 2 / g, 1.8m 2 / g, 1.9m 2 / g, 2m 2 / g, 2.2m 2 / g, 2.4m 2 / g and 2.5m 2 / g, etc.
[0058] Optionally, in some embodiments, the active particles are graphite particles.
[0059] It can be understood that the larger the specific surface area of the active particles, the more sites on the negative electrode material layer that can be used for lithium insertion or removal, and the more active sites on the negative electrode material layer. When the electrolyte 120 infiltrates the negative electrode plate 111, the electrolyte 120 is likely to undergo side reactions with lithium ions at the active sites of the negative electrode material layer.
[0060] It can be understood that the number of active particles is plural.
[0061] It can be understood that S represents the total area of the active particles per unit mass.
[0062] In this embodiment, when the specific surface area S of the active particles meets the range of: 0.8m 2 / g≤S≤2.5m 2 / g, the specific surface area S of the active particles is within a reasonable range, and there are more active sites on the negative electrode material layer, which can reduce the speed at which lithium ions in the electrolyte 120 are embedded in or removed from the negative electrode plate 111. In other words, the lithium embedding efficiency of the negative electrode plate 111 is high, so that the battery 100 has a higher energy efficiency. In addition, it can be avoided that the specific surface area of the active particles is too large to accelerate the combination of fluoride ions separated by the first additive and lithium ions, so that the battery 100 has both high energy efficiency, initial charge and discharge efficiency and energy density. When the specific surface area S of the active particles is too large, there are too many active sites on the negative electrode material layer. When the electrolyte 120 infiltrates the negative electrode plate 111, the fluoride ions separated by the first additive in the electrolyte 120 are easy to combine with lithium ions at the active sites. In other words, the more active sites there are in the negative electrode material layer, the easier it is for the fluoride ions to combine with lithium ions, thereby exacerbating the loss of lithium ions in the electrolyte 120, resulting in a lower initial charge and discharge efficiency and energy density of the battery 100. When the specific surface area S of the active particles is too small, there are too few active sites on the negative electrode material layer. In other words, the lithium insertion efficiency of the negative electrode plate 111 is low, resulting in a lower energy efficiency of the battery 100.
[0063] In some embodiments, in the electrolyte 120, the mass fraction of the first additive is a, and the mass fraction of the second additive is b; the battery 100 satisfies the relationship: 0.2 g / m 2 ≤100(a+b) / S≤8g / m 2 .
[0064] Specifically, the value of 100(a+b) / S may be, but is not limited to, 0.2 g / m 2 , 0.8g / m 2 , 1g / m 2 , 1.4g / m 2 , 2g / m 2 , 2.2g / m 2 , 2.5g / m 2 , 3g / m 2 3.5g / m 2 , 4g / m 2 4.5g / m 2 , 5g / m 2 5.5g / m 2 , 6g / m 2 , 6.4g / m 2 , 7g / m 2 , 7.2g / m 2 , 7.5g / m 2 and 8g / m 2 wait.
[0065] In this embodiment, when the battery 100 satisfies the relationship 0.2 g / m 2 ≤100(a+b) / S≤8g / m 2When, in the battery 100, the mass fraction a of the first additive, the mass fraction b of the second additive and the specific surface area S of the active particles are all within a reasonable range. When the specific surface area S of the active particles is within a reasonable range, there are more active sites on the negative electrode material layer, which can reduce the speed at which lithium ions in the electrolyte 120 are embedded in or out of the negative electrode plate 111. In other words, the lithium embedding efficiency of the negative electrode plate 111 is high, so that the battery 100 has a higher energy efficiency. In addition, the mass fractions of the first additive and the second additive are both within a reasonable range. The second additive can combine with the fluoride ions separated by the first additive to avoid the free fluoride ions from combining with the lithium ions on the active sites, thereby reducing the side reactions between the electrolyte 120 and the negative electrode material layer, and reducing the loss of lithium ions in the electrolyte 120, so that the battery 100 has a higher initial charge and discharge efficiency and energy density. Accordingly, when the specific surface area of the active particles is small, the amount of the first additive and the second additive required during the formation of the battery 100 is small. If the first additive and the second additive are too much, the SEI film on the surface of the negative electrode plate 111 may become thicker, slowing down the migration of lithium ions and affecting the energy efficiency of the battery 100. When the specific surface area of the active particles is large, the SEI film formed on the surface of the negative electrode plate 111 should be larger and thicker, and the amount of the first additive and the second additive needs to be increased accordingly. If the mass content of the first additive and the second additive is small, the first additive and the second additive cannot form a complete SEI film on the surface of the negative electrode plate 111 for interface protection, resulting in poor interface stability of the SEI film, which reduces the cycle stability of the battery 100. When 100(a+b) / S is too large, the sum of the mass fraction a of the first additive and the mass fraction b of the second additive is too large or the specific surface area S of the active particles is too small. Although the first additive and the second additive are compounded to reduce the consumption of active lithium in the electrolyte 120, when the first additive and the second additive are too much, the internal resistance of the battery 100 may be increased, and the specific surface area of the active particles is too small, so that the lithium insertion rate of the negative electrode plate 111 is slow, and ultimately the energy efficiency of the battery 100 is too low. When 100(a+b) / S is too small, the sum of the mass fraction a of the first additive and the mass fraction b of the second additive is too small or the specific surface area S of the active particles is too large, the lithium insertion rate of the negative electrode plate 111 is fast, so that the battery 100 has a higher energy efficiency. However, the side reactions between the negative electrode plate 111 and the electrolyte 120 increase to consume excessive active lithium ions in the electrolyte 120 , thereby causing the initial charge and discharge efficiency and cycle performance of the battery 100 to be too poor.
[0066] In some embodiments, the median particle size D of the active particles is in the range of 5 μm ≤ D ≤ 20 μm.
[0067] Specifically, the median particle size D of the active particles may be, but is not limited to, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, 15 μm, 16 μm, 17 μm, 18 μm, 19 μm and 20 μm, etc.
[0068] It can be understood that the particle size of the active particle is the maximum radial dimension of the active particle. Further, the particle size of the active particle is the diameter of the active particle.
[0069] It can be understood that the median particle size of the active particles is the particle size corresponding to the mass of particles smaller than this particle size accounting for 50% of the total mass of the particles on the particle size distribution curve of the active particles.
[0070] It can be understood that the smaller the median particle size of the active particles is, the larger the area of the active particles exposed in the negative electrode material layer is, the more sites on the negative electrode material layer that can be used for lithium insertion or removal, and the more active sites on the negative electrode material layer. When the electrolyte 120 infiltrates the negative electrode plate 111, the electrolyte 120 is likely to undergo side reactions with lithium ions at the active sites of the negative electrode material layer.
[0071] In this embodiment, when the median particle size D of the active particles satisfies the range of 5μm≤D≤20μm, the median particle size D of the active particles is within a reasonable range, and the number of active sites in the negative electrode material layer is within a reasonable range, which is convenient for the insertion and extraction of lithium ions, and can also avoid the increase of side reactions between the negative electrode material layer and the electrolyte 120 due to too many active sites, so that the battery 100 has both high energy efficiency, initial charge and discharge efficiency and energy density, and the battery 100 has good cycle performance. When the median particle size D of the active particles is too large, relatively, the specific surface area of the active particles is too small, then when the electrolyte 120 infiltrates the negative electrode plate 111, the channels and sites for lithium ions to be embedded in the negative electrode material layer are less, so that the lithium insertion efficiency of the negative electrode plate 111 is low, and the cycle performance and energy efficiency of the battery 100 are reduced. When the median particle size D of the active particles is too small, relatively speaking, the specific surface area of the active particles is too large. Then, when the electrolyte 120 infiltrates the negative electrode plate 111, the fluoride ions separated from the first additive in the electrolyte 120 are easy to combine with the lithium ions at the active sites. In other words, the more active sites the negative electrode material layer has, the easier it is for the fluoride ions to combine with the lithium ions, thereby aggravating the loss of lithium ions in the electrolyte 120, resulting in lower initial charge and discharge efficiency and energy density of the battery 100.
[0072] In some embodiments, in the electrolyte 120, the mass fraction of the first additive is a, and the mass fraction of the second additive is b; the negative electrode plate 111 includes a stacked negative electrode current collector layer and a negative electrode material layer, the negative electrode material layer includes active particles, and the median particle size of the active particles is D, then the battery 100 satisfies the relationship: 3μm≤D / 100(a+b)≤16μm.
[0073] Specifically, the value of D / 100(a+b) can be, but is not limited to, 3μm, 4μm, 4.5μm, 5μm, 6μm, 7μm, 8μm, 9μm, 10μm, 11μm, 12μm, 13μm, 14μm, 15μm, 16μm, etc.
[0074] When the battery 100 satisfies the relationship 3μm≤D / 100(a+b)≤16μm, in the battery 100, the mass fraction a of the first additive, the mass fraction b of the second additive and the median particle size D of the active particles are all within a reasonable range. On the one hand, the compounding of the first additive and the second additive can not only slow down the combination of the fluoride ions separated by the first additive with the lithium ions in the electrolyte 120 to avoid excessive consumption of lithium ions, but also form a stable SEI film on the surface of the negative electrode sheet 111, so that the battery 100 has both high energy density, initial charge and discharge efficiency and energy efficiency. On the other hand, the median particle size of the active particles is within a reasonable range, which can not only make the negative electrode sheet 111 have a high lithium insertion rate, but also because the first additive and the second additive are set in the electrolyte 120, it can avoid the aggravation of the side reaction of the negative electrode sheet 111 and the electrolyte 120 due to the increase of active sites in the negative electrode material layer, so that the battery 100 has high cycle stability and energy efficiency. Accordingly, when the median particle size of the active particles is small, the lithium removal rate and lithium insertion rate of the negative electrode material layer are faster, but at the same time, the structural stability of the active particles is relatively poor, and more first additives and second additives are required to form a stable SEI film at the interface between the negative electrode plate 111 and the electrolyte 120 to improve the cycle stability of the battery 100. However, at the same time, the content of the first additive and the second additive should not be too much to avoid forming an excessively thick SEI film on the surface of the negative electrode plate 111, which in turn reduces the transmission efficiency of lithium ions at the interface of the negative electrode plate 111 and reduces the energy efficiency of the battery 100. When the value of D / 100(a+b) is too large, the median particle size D of the active particles is too large or the sum of the mass fraction a of the first additive and the mass fraction b of the second additive is too small. When the median particle size of the active particles is too large, when the electrolyte 120 infiltrates the negative electrode plate 111, there are fewer channels and sites for lithium ions to be embedded in the negative electrode material layer, so that the lithium insertion efficiency of the negative electrode plate 111 is low, and the cycle performance and energy efficiency of the battery 100 are reduced. When the sum of the mass fraction a of the first additive and the mass fraction b of the second additive is too small, if the first additive is too little, it is difficult for the electrolyte 120 to form an SEI film on the surface of the negative electrode plate 111, and in the subsequent charge and discharge cycle process, it is difficult for the first additive to repair the SEI film in time, thereby reducing the cycle stability of the battery 100. If the second additive is too little, it is difficult for the second additive to combine with the fluoride ions shed by the first additive, so that it is difficult to slow down the consumption of active lithium in the electrolyte 120, so that the initial charge and discharge efficiency and energy density of the battery 100 are low.When the value of D / 100(a+b) is too small, the median particle size D of the active particles is too small or the sum of the mass fraction a of the first additive and the mass fraction b of the second additive is too large. When the median particle size of the active particles is too small, the specific surface area of the active particles is too large. Then, when the electrolyte 120 infiltrates the negative electrode plate 111, the fluoride ions separated from the first additive in the electrolyte 120 are easy to combine with lithium ions at the active sites. In other words, the more active sites the negative electrode material layer has, the easier it is for the fluoride ions to combine with lithium ions, thereby exacerbating the loss of lithium ions in the electrolyte 120, resulting in lower initial charge and discharge efficiency and energy density of the battery 100. When the sum of the mass fraction a of the first additive and the mass fraction b of the second additive is too large, when the mass fraction a of the first additive is too much, it may cause too many fluoride ions separated from the first additive. Even if the content of the second additive is relatively high, it is difficult to slow down the combination of fluoride ions and lithium ions. In addition, if the mass fraction of the second additive is large enough, the product formed by the second additive and fluoride ions will also increase the impedance of the battery 100, thereby reducing the energy efficiency of the battery 100.
[0075] The technical solution of this application is further introduced in the following with multiple embodiments:
[0076] Example 1 to Example 10, Comparative Example 1 to Comparative Example 7:
[0077] 1. Preparation of electrolyte 120:
[0078] In an argon atmosphere glove box with a moisture content of ≤1ppm, ethylene carbonate, dimethyl carbonate, and ethyl methyl carbonate are uniformly stirred and mixed in a mass ratio of 1:1:1, and the dried electrolyte lithium salt lithium hexafluorophosphate is dissolved in the solvent and fully dissolved. The lithium salt concentration is 1 moL / L, and then a first additive and a second additive are added, wherein the first additive is fluoroethylene carbonate, and the second additive is 2-[N,N-bis(trifluoromethanesulfonyl)amino]pyridine, to obtain the electrolyte 120 of Examples 1 to 10 and Comparative Examples 1 to 7, wherein in the electrolyte 120 of Examples 1 to 10 and Comparative Examples 1 to 7, the mass fraction a of the first additive and the mass fraction b of the second additive are as shown in Table 1.
[0079] 2. Preparation of negative electrode sheet 111:
[0080] The negative electrode active particles artificial graphite, thickener sodium carboxymethyl cellulose (CMC), conductive carbon black (Super-P) and binder styrene butadiene rubber latex (SBR) are mixed in a mass ratio of 96:2:1:1, deionized water is added, and a negative electrode slurry with a solid content of 50wt% is prepared, and stirred evenly. The negative electrode slurry is evenly coated on one surface of a negative electrode current collector layer (copper foil) with a thickness of 6μm, and a negative electrode material layer is obtained after drying. After further cold pressing, stripping, and cutting, the negative electrode sheets 111 of Examples 1 to 10 and Comparative Examples 1 to 7 are obtained. The single-sided thickness of the negative electrode material layer is 70μm. Among them, the specific surface area S and median particle size D of the active particles in the negative electrode sheets 111 of Examples 1 to 10 and Comparative Examples 1 to 7 are shown in Table 1.
[0081] Furthermore, the value of a / b, the value of 100(a+b) / S, and the value of D / 100(a+b) are shown in Table 1.
[0082] 3. Preparation of positive electrode sheet 113:
[0083] The positive electrode active material lithium iron phosphate (LiFePO 4 ), conductive carbon black (Super-P), and binder PVDF are mixed in a mass ratio of 97.2:2.3:0.5; then N-methylpyrrolidone (NMP) is added as a solvent to prepare a positive electrode slurry with a solid content of 60wt%, and stirred evenly, and then the positive electrode slurry is evenly coated on one surface of a positive electrode current collector layer (aluminum foil) with a thickness of 10μm, and then dried to obtain a positive electrode material layer, and after further cold pressing, striping, and cutting, a positive electrode sheet 113 is obtained. The single-sided thickness of the positive electrode material layer is 100μm.
[0084] 4. Preparation of the diaphragm 112:
[0085] The separator 112 is a 16 um polyethylene (PE) film.
[0086] 5. Assembly of battery 100:
[0087] The positive electrode sheet 113, the separator 112, and the negative electrode sheet 111 are stacked in order so that the separator 112 is located between the positive electrode sheet 113 and the negative electrode sheet 111 to play an isolating role, and then they are wound into a bare electrode assembly 110; after welding the pole ears, the bare battery 100 is placed in an outer packaging shell, and after drying, the above-mentioned electrolyte 120 is injected, and after vacuum packaging, standing, forming, shaping, etc., the implementation batteries 1 to 10 and the comparison batteries 1 to 7 are finally prepared.
[0088] Among them, the electrolyte 120 and the negative electrode plate 111 of Example 1 are assembled in the implementation battery 1, the electrolyte 120 and the negative electrode plate 111 of Example 2 are assembled in the implementation battery 2, the electrolyte 120 and the negative electrode plate 111 of the comparative example 1 are assembled in the comparative battery 1, the electrolyte 120 and the negative electrode plate 111 of the comparative example 2 are assembled in the comparative battery 2, and so on.
[0089] Table 1: Performance parameters of the electrolyte 120 and performance parameters of the active particles of Examples 1 to 10 and Comparative Examples 1 to 7.
[0090]
[0091]
[0092] Performance test of battery 100:
[0093] Charge and discharge cycle test:
[0094] The above-mentioned implementation batteries 1 to implementation batteries 10 and comparison batteries 1 to comparison batteries 7 were subjected to constant current charge and discharge cycle tests on a charge and discharge instrument. The test temperature was 45°C, the charge and discharge rate was 1C (the size of the charge and discharge current is usually expressed by the charge and discharge rate, and the calculation formula of the charge and discharge current is: charge and discharge current = charge and discharge rate × rated capacity of battery 100), and the charge and discharge voltage window was 2.5V~3.65V (that is, the charging cut-off voltage of battery 100 is 3.65V, and the discharging cut-off voltage of battery 100 is 2.5V); the capacity retention rate and energy efficiency of implementation batteries 1 to implementation batteries 10 and comparison batteries 1 to comparison batteries 7 after 800 cycles were calculated. The values of the first coulomb efficiency of implementation batteries 1 to implementation batteries 10 and comparison batteries 1 to comparison batteries 7 at 45°C, the values of the capacity retention rate after 800 cycles, and the values of the energy efficiency are shown in Table 2.
[0095] The calculation formula is: capacity retention rate after the nth cycle = (discharge capacity after the nth cycle / discharge capacity of the first cycle) × 100%; energy efficiency of the nth cycle = (discharge energy of the nth cycle / charge energy of the nth cycle) × 100%. In particular, the first coulomb efficiency = energy efficiency of the first cycle = discharge energy of the first cycle / charge energy of the first cycle.
[0096] A complete charge and discharge is usually called a charge and discharge cycle, that is, the battery 100 is first charged from 2.5V to 3.65V, and then discharged from 3.65V to 2.5V, thus forming a charge and discharge cycle. Cycle N times means repeating the above process N times.
[0097] Table 2: Performance parameters of implementation battery 1 to implementation battery 10 and comparison battery 1 to comparison battery 7:
[0098]
[0099] It can be understood that the first coulombic efficiency can represent the first charge and discharge efficiency of the battery 100 .
[0100] Please refer to Table 1 and Table 2. It can be seen from the data of Examples 1 to 3 and Comparative Examples 1 to 3 that, under the same other conditions, the electrolyte 120 of Examples 1 to 3 includes the first additive and the second additive, and the mass fraction b of the second additive in the electrolyte 120 of Examples 1 to 3 meets a reasonable range. The electrolyte 120 of Comparative Example 1 only includes the first additive and does not include the second additive. The mass fraction of the second additive in the electrolyte 120 of Comparative Example 2 is too large, and the mass fraction of the second additive in Comparative Example 3 is too small, which makes the first coulomb efficiency of Implementation Battery 1 to Implementation Battery 3 higher than the first coulomb efficiency of Comparative Battery 1 to Comparative Battery 3, and the capacity retention rate of Implementation Battery 1 to Implementation Battery 3 at 45°C and 1P cycle 800 cycles is higher than the capacity retention rate of Comparative Battery 1 to Comparative Battery 3 at 45°C and 1P cycle 800 cycles. The energy efficiency of the implementation battery 1 to the implementation battery 3 after 800 cycles at 45°C and 1P is higher than that of the comparison battery 1 and the comparison battery 2 after 800 cycles at 45°C and 1P. The energy efficiency of the comparison battery 3 after 800 cycles at 45°C and 1P is higher. This is because: the electrolyte 120 of the embodiments 1 to 3 includes the second additive and the mass fraction of the second additive is within a reasonable range. In the formation stage of the battery 100, the first additive and the second additive are compounded, the number of pyridine carbon cations separated from the second additive and the number of N,N-bistrifluoromethanesulfonyl are both within a reasonable range, the pyridine carbon cations of the second additive are combined with the fluoride ions separated from the first additive to reduce the free fluoride ions in the electrolyte 120, so that the battery 100 has a higher initial charge and discharge efficiency and energy density. In addition, the product of the combination of the first additive and the second additive, 2-fluoropyridine, has a higher reactivity than the first additive, and is easier to decompose into a film on the surface of the negative electrode plate 111, and N, N-bistrifluoromethanesulfonyl can promote the ring opening and decomposition of ethylene carbonate molecules, so that the first additive and the second additive are better decomposed into a film on the surface of the negative electrode plate 111 to maintain the stability of the SEI film, so that the implementation battery 1 to the implementation battery 3 still have a high capacity retention rate and energy efficiency after 800 cycles at 45°C and 1P. Furthermore, the first additive and the second additive form an inorganic and organic composite interface film containing N, F and C on the surface of the negative electrode plate 111, so that the battery 100 has good cycle stability. When the mass fraction of the second additive is too large, the second additive separates too much 2-fluoropyridine, and the pyridine carbon cations in the second additive and the fluoride ions in the first additive form too much 2-fluoropyridine, which will increase the impedance of the interface film between the negative electrode plate 111 and the electrolyte 120, thereby making the energy efficiency of the comparison battery 2 too low.When the mass fraction of the second additive is too small, too few pyridinium cations are separated from the second additive, and the pyridinium cations are insufficient to combine with the fluoride ions one by one, so that free fluoride ions are still present in the electrolyte 120. The fluoride ions will combine with the lithium ions in the electrolyte 120 to form lithium fluoride, causing the loss of lithium ions in the electrolyte 120, so that when the electrolyte 120 is applied to the battery 100, the initial charge and discharge efficiency and energy density of the battery 100 are low.
[0101] From the data of Example 2, Example 4 and Example 5, it can be seen that the electrolyte 120 of Example 2, Example 4 and Example 5 all include the first additive and the mass fraction of the first additive is within a reasonable range, and the value of a / b, the value of 100(a+b) / S and the value of D / 100(a+b) are all within a reasonable range, so that the implementation battery 2, the implementation battery 4 and the implementation battery 5 all have high energy efficiency and cycle performance. Further, under the same other conditions, as the mass fraction of the first additive continues to increase, the first coulomb efficiency of the corresponding battery 100 increases first and then decreases, and the capacity retention rate of the battery 100 at 45°C and 1P cycles for 800 cycles shows an upward trend, but the energy efficiency of the corresponding battery 100 shows a downward trend. This is because: when the mass fraction of the second additive remains unchanged, as the mass fraction of the first additive increases, the fluoride ions separated by the first additive increase. In the formation stage of the battery 100, the pyridinium cations separated by the second additive are combined with the fluoride ions one by one to slow down the consumption of lithium ions in the electrolyte 120 by the fluoride ions. When the mass fraction of the first additive is relatively small, the pyridinium cations separated by the second additive can quickly combine with the fluoride ions separated by the first additive, thereby avoiding the consumption of lithium ions and improving the initial coulombic efficiency and capacity retention rate of the battery 100. As the mass fraction of the first additive increases, the product formed by the combination of the fluoride ions separated by the first additive and the pyridinium cations of the second additive increases the internal resistance of the battery 100 and reduces the initial coulombic efficiency of the battery 100. Accordingly, during the charge and discharge cycle of the battery 100, the product 2-fluoropyridine formed by the combination of fluoride ions and pyridinium cations will increase the impedance of the interface film between the negative electrode plate 111 and the electrolyte 120, thereby gradually reducing the energy efficiency of the implementation battery 4, the implementation battery 2, and the implementation battery 5.
[0102] Similarly, it can be seen from the data of Example 8 and Comparative Example 5 that, under the same other conditions, the mass fraction a of the first additive in Example 8 is within a reasonable range, and the mass fraction of the first additive in Comparative Example 5 is too small, so that the first coulombic efficiency, the capacity retention rate after 800 cycles at 45°C and 1P, and the energy efficiency after 800 cycles at 45°C and 1P of the implementation battery 8 are higher than the first coulombic efficiency, the capacity retention rate after 800 cycles at 45°C and 1P, and the energy efficiency after 800 cycles at 45°C and 1P of the comparative battery 5, respectively. This is because: in the comparative battery 5, the mass fraction of the first additive is too small, although the consumption of lithium ions by fluoride ions separated by the first additive is reduced, but at the same time, the first additive cannot be compounded with the second additive, and the first additive and the second additive are difficult to form a stable SEI film on the surface of the negative electrode plate 111, and in the subsequent charge and discharge cycles of the battery 100, the first additive is also difficult to repair the SEI film, which increases the internal resistance of the battery 100 and reduces the capacity retention rate and energy efficiency of the comparative battery 5.
[0103] It can be seen from the data of Example 6, Example 7 and Comparative Example 4 that when the specific surface area and median particle size of the active particles are the same, the mass fraction of the first additive and the mass fraction of the second additive can be adjusted to make the corresponding battery 100 have a higher initial charge and discharge efficiency and energy density. Specifically, in Example 6 and Example 7, 100(a+b) / S meets a reasonable range, while in Comparative Example 4, the value of 100(a+b) / S is too large, which makes: the first additive and the second additive compound, although it can reduce the consumption of active lithium in the electrolyte 120, but when the first additive and the second additive are too much, it may increase the internal resistance of the battery 100, and the specific surface area of the active particles is too small, so that the lithium insertion rate of the negative electrode plate 111 is slow, and finally the energy efficiency of the battery 100 is too low, so that the final energy efficiency of the comparative battery 4 is low.
[0104] From the data of Example 9, Example 10 and Comparative Example 6, it can be seen that the median particle size of the active particles and the value of D / 100(a+b) in Example 9 and Example 10 are both within a reasonable range, and the median particle size of the active particles and the value of D / 100(a+b) in Comparative Example 6 are both too small, so that the first coulomb efficiency of the implementation battery 9 and the implementation battery 10 is higher than the first coulomb efficiency of the comparative battery 6, and the capacity retention rate of the implementation battery 9 and the implementation battery 10 at 45°C and 1P cycle 800 cycles is higher than that of the comparative battery 6 at 45°C and 1P cycle 800 cycles. The energy efficiency of the implementation battery 9 and the implementation battery 10 after 800 cycles at 45°C and 1P is higher than that of the comparative battery 6 after 800 cycles at 45°C and 1P. This is because: the number of active sites in the negative electrode material layer is within a reasonable range, which is convenient for the insertion and extraction of lithium ions, and can also avoid the increase of the side reaction between the negative electrode material layer and the electrolyte 120 due to too many active sites, so that the battery 100 has both high energy efficiency, initial charge and discharge efficiency and energy density, and the battery 100 has good cycle performance. When the median particle size of the active particles is too small, when the electrolyte 120 infiltrates the negative electrode plate 111, the fluorine ions separated from the first additive in the electrolyte 120 are easy to combine with lithium ions at the active sites. In other words, the more active sites in the negative electrode material layer, the easier it is for the fluorine ions to combine with lithium ions, thereby exacerbating the loss of lithium ions in the electrolyte 120, so that the initial charge and discharge efficiency and energy density of the battery 100 are low.
[0105] Similarly, from the data of Example 8 and Comparative Example 7, it can be seen that the median particle size of the active particles and the value of D / 100(a+b) in Example 8 are both within a reasonable range, and the median particle size of the active particles and the value of D / 100(a+b) in Comparative Example 7 are both too large, so that the first coulomb efficiency of the implementation battery 8 is higher than the first coulomb efficiency of the comparative battery 7, the capacity retention rate of the implementation battery 8 at 45°C and 1P cycles for 800 cycles is higher than the capacity retention rate of the comparative battery 7 at 45°C and 1P cycles for 800 cycles, and the implementation battery The energy efficiency of cell 8 after 800 cycles at 45°C and 1P is higher than that of comparison cell 7 after 800 cycles at 45°C and 1P. This is because: the number of active sites in the negative electrode material layer is within a reasonable range, which is convenient for the insertion and extraction of lithium ions, and can also avoid the increase of side reactions between the negative electrode material layer and the electrolyte 120 due to too many active sites, so that the battery 100 has both high energy efficiency, initial charge and discharge efficiency and energy density, and the battery 100 has good cycle performance. When the median particle size of the active particles is too large, when the electrolyte 120 infiltrates the negative electrode plate 111, there are fewer channels and sites for lithium ions to be embedded in the negative electrode material layer, so that the lithium insertion efficiency of the negative electrode plate 111 is low, and the cycle performance and energy efficiency of the battery 100 are reduced.
[0106] See also Figure 2 and Figure 3 The present application also provides an electrical device 200 , which includes a device body 210 and a battery 100 provided in the present application, and the battery 100 supplies power to the device body 210 .
[0107] It can be understood that the battery 100 is electrically connected to the device body 210 .
[0108] In this embodiment, the battery 100 has high initial charge and discharge efficiency, energy density and energy efficiency, so that the battery 100 can provide stable power to the device body 210, which is beneficial to improving the user experience.
[0109] Optionally, the power-consuming device 200 of the embodiment of the present application may be, but is not limited to, a portable electronic device such as a mobile phone, a tablet computer, a laptop computer, a desktop computer, a smart bracelet, a smart watch, an e-reader, a game console, etc. It may also be a vehicle such as a car, a truck, a car, a truck, a truck, a motor vehicle, a high-speed train, an electric vehicle, etc. In addition, it may also be various household appliances, etc. The present application Figure 2 The electrical equipment 200 of the embodiment is an energy storage battery cabinet.
[0110] It can be understood that the electric device 200 described in this embodiment is only one form of the electric device 200 used by the battery 100, and should not be understood as a limitation on the electric device 200 provided in this application, nor should it be understood as a limitation on the electric device 200 provided in each embodiment of this application.
[0111] Mentioning "embodiment" and "implementation method" in this application means that the specific features, structures or characteristics described in conjunction with the embodiment may be included in at least one embodiment of the present application. The appearance of the phrases in various places in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described in this application can be combined with other embodiments. In addition, it should also be understood that the features, structures or characteristics described in the various embodiments of the present application can be arbitrarily combined to form another embodiment that does not deviate from the spirit and scope of the technical solution of the present application, provided that there is no contradiction between them.
[0112] Finally, it should be noted that the above implementation modes are only used to illustrate the technical solution of the present application and are not intended to limit it. Although the present application has been described in detail with reference to the above preferred implementation modes, a person of ordinary skill in the art should understand that the technical solution of the present application may be modified or replaced by equivalents without departing from the spirit and scope of the technical solution of the present application.
Claims
1. An electrolyte, characterized in that: The electrolyte includes: a first additive and a second additive, wherein the first additive includes fluoroethylene carbonate, and the second additive includes 2-[N,N-bis(trifluoromethanesulfonyl)amino]pyridine.
2. The electrolyte according to claim 1, characterized in that The mass fraction of the first additive is a, and the mass fraction of the second additive is b, then the electrolyte satisfies the relationship: 1<a / b≤10.
3. The electrolyte according to claim 2, characterized in that The mass fraction a of the first additive is in the range of 0.1%≤a≤3%.
4. The electrolyte according to claim 2, characterized in that The mass fraction b of the second additive is in the range of 0.05%≤b≤2%.
5. A battery, characterized in that: The battery comprises: An electrode assembly, the electrode assembly comprising a negative electrode sheet; and The electrolyte according to any one of claims 1 to 4, wherein the electrolyte is used to wet at least a portion of the electrode assembly.
6. The battery according to claim 5, characterized in that In the electrolyte, the mass fraction of the first additive is a, and the mass fraction of the second additive is b; the negative electrode plate includes a negative electrode current collector layer and a negative electrode material layer stacked, and the negative electrode material layer includes active particles, and the specific surface area of the active particles is S, then the battery satisfies the relationship: 0.2g / m 2 ≤100(a+b) / S≤8g / m 2 .
7. The battery according to claim 6, characterized in that The specific surface area S of the active particles is in the range of: 0.8m 2 / g≤S≤2.5m 2 / g.
8. The battery according to claim 5, characterized in that In the electrolyte, the mass fraction of the first additive is a, and the mass fraction of the second additive is b; the negative electrode plate includes a negative electrode current collector layer and a negative electrode material layer stacked together, the negative electrode material layer includes active particles, and the median particle size of the active particles is D, then the battery satisfies the relationship: 3μm≤D / 100(a+b)≤16μm.
9. The battery according to claim 8, characterized in that The range of the median particle size D of the active particles is: 5 μm≤D≤20 μm.
10. An electrical device, characterized in that: The electrical equipment includes: The device itself; and The battery according to any one of claims 5 to 9, wherein the battery is used to supply power to the device body.
Citation Information
Patent Citations
Lithium ion battery electrolyte and lithium ion battery using same
CN105845984A
Lithium secondary battery electrolyte solution and lithium secondary battery containing lithium secondary battery electrolyte solution
CN108539270A
Novel trifluoromethanesulfonamide lithium salt as well as preparation method and application thereof
CN112062715A
Low-temperature electrolyte and high-energy-density high-voltage lithium ion battery thereof
CN116053580A
Electrolyte, battery and electric equipment
CN117691189A